2023
DOI: 10.1021/acsomega.3c00704
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Essential Oils from Nepeta transcaucasica Grossh. and Nepeta cataria L. Cultivated in Bulgaria and Their Antimicrobial and Antioxidant Activity

Abstract: The genus Nepeta, belonging to the family Lamiaceae, includes about 300 species, most of which are used in folk medicine due to their pronounced biological properties. The aim of the present study was to evaluate the agrobiological characteristics of Nepeta transcaucasica (N. transcaucasica) Grossh. and Nepeta cataria (N. cataria) L., cultivated in Bulgaria, and obtain their essential oils and determine their antimicrobial and antioxidant activities. The agrobiological characteristics of the two species growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(128 reference statements)
1
2
0
Order By: Relevance
“…This observation can be attributed to the strong antioxidative property of CO, as reported earlier in the liver [ 32 ], kidney [ 33 ], and brain [ 34 ]. Our results are consistent with those of other studies that made comparable observations on natural oils that had antioxidant properties [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…This observation can be attributed to the strong antioxidative property of CO, as reported earlier in the liver [ 32 ], kidney [ 33 ], and brain [ 34 ]. Our results are consistent with those of other studies that made comparable observations on natural oils that had antioxidant properties [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…The activity of ME and EO was found to be comparable with the standard ascorbic acid at higher concentrations. This may be attributed to the presence of compounds found in this study possessing antioxidation properties such as neophytadiene, β-sitosterol (ME) and diisooctyl phthalate (EO). ,, Several studies have reported the antioxidant property of natural products of plants . The antioxidation property is beneficial in scavenging free radicals involved in several diseases and metabolic pathways and imparts immunoprotective, hepatoprotective, and neuroprotective effects …”
Section: Results and Discussionmentioning
confidence: 73%
“…These results are similar to ME and emphasizes the importance of EO as an effective antimicrobial. The major compounds detected by GC-MS in EO summarized in Table indicate the presence of bioactive compounds such as stearyl alcohol, cis -9-tetradecenoic acid, isobutyl ester, butyl 9-tetradecenoate, 11,13-dimethyl-12-tetradecen-1-ol acetate, and diisooctyl phthalate that demonstrated antibacterial activity and may be responsible for the achieved inhibition by EO. , C . albicans exhibited an inhibition range of 33–53.7%.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It can be propagated only vegetatively, by cuttings or by division. The essential oil contains nepetalactone, germacrene, citral, citronellol, geraniol, nerol, mucilage, saponins, etc., and it exhibited antioxidant activity and antibacterial properties against Escherichia coli microorganisms [ MOLLOVA & al. 2023].…”
Section: Resultsmentioning
confidence: 99%